Mesias Raja: Simbol Kedaulatan yang Menggema di Seluruh Dunia - Nggebu, Sostenis; Kanu, Zevrijn Boy; Pote, Dominggu; Siwabessy, Donald; Lestari, Sonia (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2023)
The Apostle Paul as God's chosen figure to proclaim Jesus as the Messiah King who brings salvation to all nations. People who are still outside of Christ can hear the Gospel that sets them free from sin. Getting to know the Messiah King personally also serves to build a bridge of communication to people who don't believe. So the purpose of this study is to explain the Messiah King who was preached by the apostle Paul. The method used is a descriptive study. The results show that Paul was very fascinated by the person of Jesus as the Messiah King who appeared to him on the way to Damascus. Since the introduction of Jesus Christ, Paul has been active in preaching the Messiah King to nations outside the Jewish nation. He also disassembled and rearranged his concept of faith and theological views of his mission. Christ who triumphed over death became the basis for Paul's theological views. Paul's preaching work served as the basis for the Church to preach that Jesus Christ is the Savior for all mankind.